The effect of core stability exercise and functional ability for prevention of recurrences of low‐back pain in patients with herniated nucleus pulposus - Nursaputri Nursaputri; Wahyu Tri Sudaryanto (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: An intervertebral disc's nucleus pulposus or annulus fibrosus may protrude in part or in its entirety in a condition known as herniated nucleus pulposus (HNP). This can put pressure on the spinal canal or nerve roots through the annulus fibrosus's tear. Over 90% of HNP instances take place in the disc between the L4-L5 lumbar vertebrae or the L5-S1 sacral vertebrae, which is the disc between the fourth and fifth lumbar (L4-L5) vertebrae, which means that pressure is exerted on the L4, L5 and S1 nerves, causing local low back pain and radicular pain in the lower limbs, especially in the back of the lower leg and in the back of the foot. Purpose: To determine the effect of core stability exercise on reducing pain and increasing functional ability in LBP EC HNP patients. Method: A quantitative research method in the form of Quasy Experimental with a Two Group Pretest-Posttest design, namely a control group and a group of 20 respondents who experienced LBP EC HNP. The research instrument uses the ODI questionnaire and Visual Analog Scale (VAS). The data obtained were then analyzed using the Wilcoxon test and the Mann Whitney test. Results: There is a difference in the influence of ODI and Motion Pain between group 1 control and group 2 treatment (p <0.05). While in the pressure pain value (p > 0.05) then the decision was taken to fail to reject H0 which means there is no difference in the influence of pressure pain between group 1 control and group 2 treatment. Conclusion: There is an effect of Core Stability Exercise on reducing pain and increasing the ability of functional activities of daily living in patients with Lumbar Hernia Nucleus Pulposus.